Clinical Bioethics - Adolescence and alimentary behaviour: ethical trends and educational strategies. - Marinozzi, Lorenza (Medicina e Morale, 1998)
In this article, the author makes an accurate nosographic analysis of diet problem diseases - presenting two clinical cases - and maintains that nervosa anorexia and nervosa bulimy are emergences of a single illness, despite of the diversity of symptoms. This disease particularly affects teenagerhood and has social and cultural roots. The actual epidemy is the reflection of our present time ambiguities, contradictions, and dream-like unreachable models. A separate chapter - dedicated to ethical considerations - highlights some precautionary measures proposals, besides the healing ones. On this points, it comes out the role of parents: they have to be the guides, the ones who point at the right way without imposing it. The guidelines to be followed are love, listening, attention, together with the recovery of such values as the "working committment", the "courage to face obstacles", the "patience to wait".